Science fiction the best of 2003 - Haber, Karen; Strahan, Jonathan
Bringing together writers such as Christopher Priest, Brian W. Aldiss, Ian MacLeod and Orson Scott Card, "Science Fiction: the best of 2003", also showcases the best writing from magazines and the Internet.